PREVALENSI DAN FAKTOR RISIKO INFEKSI Toxocara cati PADA KUCING PELIHARAAN DI KOTA BOGOR (Prevalence and Risk Factors of Toxocara cati Infection in Bogor Pet Cats) - Murniati Murniati; Etih Sudarnika; Yusuf Ridwan (Universitas Syiah Kuala, 2016)
The aims of this research were to estimate the prevalence and to determine the risk factors related to Toxocara cati (T. cati) infection in pet cats in Bogor. This study was cross sectional study using two types of data; laboratory examination results of feces samples and interview results of the cat owner using a structured questionnaires including characteristics of pet owner and pet care management. The data obtained from this study was analyzed using chi-square test. The results showed that 85 of 243 cats were positively infected by T. cati with 35% prevalence. The significant risk factor associated with the T. cati infection were: sex, sand provided, deworming and type of feed. Pet care management in Kota Bogor were well managed, however the prevalence of T. cati infection was still high. Therefore it can be a potential public health problem especially on cat owners.